2010
DOI: 10.1088/0004-637x/709/2/572
|View full text |Cite
|
Sign up to set email alerts
|

A MULTIWAVELENGTH STUDY OF A SAMPLE OF 70 μm SELECTED GALAXIES IN THE COSMOS FIELD. I. SPECTRAL ENERGY DISTRIBUTIONS AND LUMINOSITIES

Abstract: We present a large robust sample of 1503 reliable and unconfused 70 µm selected sources from the multiwavelength data set of the Cosmic Evolution Survey (COSMOS). Using the Spitzer IRAC and MIPS photometry, we estimate the total infrared luminosity, L IR (8-1000 µm), by finding the best fit template from several different template libraries. The long wavelength 70 and 160 µm data allow us to obtain a reliable estimate of L IR , accurate to within 0.2 and 0.05 dex, respectively. The 70 µm data point enables a s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
100
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(118 citation statements)
references
References 86 publications
18
100
0
Order By: Relevance
“…Still, the redshift evolution of these fractions was investigated in J13 by comparing their observed 70 μm-selected sample to an equivalently selected sample drawn from Sloan Digital Sky Survey (SDSS), finding essentially no evolution in the AGN fraction of IR-selected sources as a function of L TIR between the redshifts of 0.05 < z < 1. Here, we broadly reaffirm the results found by Kartaltepe et al (2010a) and J13 using a sample limited to the host galaxies of more powerful AGN. Considering only a SPIRE volumelimited sample between 0 < z < 1.5, a redshift range in which A90, page 32 of 39 a volume-limited sample does not restrict us only to ULIRGs, the fraction of galaxies hosting any type of AGN at the highest SFRs (equal to log(L TIR ) ∼ 12.5) is ∼60%, roughly equivalent to that found at the same L TIR in J13 and identical within the errors to the fraction computed for low-redshift IR-selected sources.…”
Section: The Role Of Agn In Starbursting Galaxiessupporting
confidence: 88%
See 1 more Smart Citation
“…Still, the redshift evolution of these fractions was investigated in J13 by comparing their observed 70 μm-selected sample to an equivalently selected sample drawn from Sloan Digital Sky Survey (SDSS), finding essentially no evolution in the AGN fraction of IR-selected sources as a function of L TIR between the redshifts of 0.05 < z < 1. Here, we broadly reaffirm the results found by Kartaltepe et al (2010a) and J13 using a sample limited to the host galaxies of more powerful AGN. Considering only a SPIRE volumelimited sample between 0 < z < 1.5, a redshift range in which A90, page 32 of 39 a volume-limited sample does not restrict us only to ULIRGs, the fraction of galaxies hosting any type of AGN at the highest SFRs (equal to log(L TIR ) ∼ 12.5) is ∼60%, roughly equivalent to that found at the same L TIR in J13 and identical within the errors to the fraction computed for low-redshift IR-selected sources.…”
Section: The Role Of Agn In Starbursting Galaxiessupporting
confidence: 88%
“…This is not the first time this trend has been observed. In two different studies covering different fields, Kartaltepe et al (2010a) and Juneau et al (2013;hereafter J13) observed that the fraction of galaxies which host AGN, AGN selected by a wide variety of methods, was a strong function of L TIR (see also the review of this trend for galaxies hosting X-ray AGN in Lapi et al 2014). These samples were, however, selected at shorter wavelengths, meaning that the contamination to L TIR from the AGN was more problematic than it is in a SPIRE-selected sample.…”
Section: The Role Of Agn In Starbursting Galaxiesmentioning
confidence: 99%
“…Indeed, the conversion of the 24 µm luminosity to total IR luminiosity becomes uncertain for ULIRGs (i.e., for L IR ≥ 10 12 L , see Bavouzet et al 2008;Goto et al 2011). Also, the merger nature of ULIRGs at low z (Kartaltepe et al 2010) makes predictions inaccurate in absence of a complete set of far-IR observations.…”
Section: Dependence Of the Predicted Ir Luminosity With Physical Galamentioning
confidence: 99%
“…The broad wavelength coverage from UV to FIR allows us to probe multiple regimes of energy and therefore to better isolate Kartaltepe et al (2010), making use of Spitzer data. The blue squares denote the GOODS samples from Elbaz et al (2011) and the dark green dots represent the selection from Symeonidis et al (2013), both making use of Herschel data.…”
Section: Models Fitting Procedure and Template Librariesmentioning
confidence: 99%